Pengaruh Pelatihan Tanggap Darurat Terhadap Kesiapsiagaan Karyawan di Lingkungan Kerja (IJM: Journal of Multidisiplinary, 2025)
This study aims to conduct an in-depth analysis of the impact of emergency response training on enhancing employee preparedness across various industrial sectors, including manufacturing, mining, and public services. The research employs a systematic review approach by examining a range of scholarly publications, professional articles, and research reports from credible and relevant sources. The findings reveal that emergency response training significantly contributes to improving employees’ cognitive (procedural knowledge), affective (awareness and concern for risk), and psychomotor (skills to act quickly and accurately) domains. Practical training methods, such as simulations and regular drills, are found to be more effective than purely theoretical training, as they help enhance mental readiness and instinctive responses in critical situations such as fires, earthquakes, chemical spills, and workplace accidents. Management support and the integration of training into the company’s occupational safety policy are identified as key success factors. Based on these findings, the study recommends that companies implement emergency response training on a regular, structured, and measurable basis as an integral part of the Occupational Health and Safety Management System.